Estudo de caso da oscilação MADDEN - JULIAN e sua influência variabilidade climática intrasazonal Amazônia e Nordeste Brasileiro - TEIXEIRA, Gleyciano Mendes (2019)
Observational data analyzed in this study showed that the rainy season during 1992 and 1994 years were characterized by a seasonal precipitation pattern predominantly drier and wetter than normal, respectively, in association with unfavorable (favorable) SST conditions verified in the intertropical Atlantic. Based on case studies, the intraseasonal variations (as estimated from weekly means) of tropical convection and precipitation over Amazon and Brazil Northeast related to propagation of the Madden-Julian oscillation (OMJ), before and during its passage through South America were investigated. The results showed that there are significant intraseasonal variations induced by the OMJ, independent of the Atlantic seasonal modulation to be favorable or unfavorable to the seasonal precipitation. Therefore, even in years with abundant rainfall observed during the rainy season (as observed in 1994) or with deficient rainfall (as observed in 1992), the passage of OMJ can effectively change the convective activity associated with Inter Tropical Convergence and Zone and Convergence Zone of the South Atlantic and thus change the sign of regional precipitation.